The impact of bank lending on Palestine economic growth: An econometric analysis of time series data - Ibrahim Mohammed Awad; Mohammed S. Al Karaki (Financial Innovation, 2019)
Banking is an essential sector of Palestine's economy. More credits provided by banks are considered to have a positive impact on economic growth so that the overall objective of this study is to examine the impact of bank lending on economic growth in Palestine. The study employs the Augmented Dickey-Fuller to test for stationarity in the time series, The Johansen co-integration, Vector Autoregressive Model and Vector Error Correction Model are employed to identify the long-run and short-run dynamics among the variables, and Granger causality test in order to determine the direction of causality. The study finds that a long run relationship exists among the variables and insignificant short run relationship. Also, the study findings show that there is unidirectional causality and runs from GDP to bank lending. The insignificant contribution of bank lending to GDP is attributed to the fact that banks are not highly interested in lending to the production sector of the economy due to the high level of risk. However, the primary empirical evidence reveals that bank lending doesn't cause economic growth, but economic growth causes bank lending.
Keywords: 650; Economic growth; Error correction model; Bank lending; Granger causality test; Palestine; Unit root tests; Solow growth model